2019
DOI: 10.1177/1354816619840845
|View full text |Cite
|
Sign up to set email alerts
|

Modelling tourist expenditure at origin and destination

Abstract: This article proposes a model of foreign tourist expenditure, based on expenditure in the country of origin (i.e. reservation of accommodation and transport) and on goods and services at the destination. The study focuses on two measures reflecting the two types of expenditure: the tourist budget share and the difference in growth rates between expenditure at origin and at destination. The random nature of each of these variables is taken into account. The tourist budget share is determined using a fractional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…Among the variables reflecting vacation characteristics, positive significant coefficients were obtained for group size and booking in advance. According to Gómez-Déniz et al (2020), although tourists who travel in a group often obtain a slight reduction in cost, they spend more at the destination, which supports the results of our analysis. Following Brida et al (2013) regarding the effect of group size on tourism expenditure, it seems reasonable to assume that when the total rental cost of a car depends on the number of people travelling together, the per capita expenditure will decrease as the number of travellers increases.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Among the variables reflecting vacation characteristics, positive significant coefficients were obtained for group size and booking in advance. According to Gómez-Déniz et al (2020), although tourists who travel in a group often obtain a slight reduction in cost, they spend more at the destination, which supports the results of our analysis. Following Brida et al (2013) regarding the effect of group size on tourism expenditure, it seems reasonable to assume that when the total rental cost of a car depends on the number of people travelling together, the per capita expenditure will decrease as the number of travellers increases.…”
Section: Resultssupporting
confidence: 87%
“…These two variables were also considered separately by Gómez-Déniz et al (2020), who suggest that each may produce different effects. In this respect, Aguiló et al (2017) observed a negative relationship between daily expenditure on transport at the destination and the reason for the trip, when this was to spend most of the time at the beach.…”
Section: Resultsmentioning
confidence: 99%
“…Within a related context, Gómez‐Déniz et al. (2020) analyze the expenditures of British and German tourists to the Canary Islands via a fractional response model, while differentiating between tourists’ budget shares at the country of origin and destination. Results confirm that the use of low‐cost carriers increases budget shares at the destination.…”
Section: Literaturementioning
confidence: 99%
“…The most recent studies on the British tourists focus on the British consumer's willingness to pay for tourism taxation (Seetaram, Song, Ye & Page, 2018). Song, Seetaram & Ye (2019) study the budget allocation of British travellers and Gómez-Déniz, Pérez-Rodríguez & Boza-Chirino (2019) analyse the expenditure patterns of British tourists in Canary Islands.…”
Section: Introductionmentioning
confidence: 99%
“…This is one of the first studies which perform the analysis on British outbound expenditure and unlike previous studies the results are not destination specific. For example, Gómez-Déniz et al(2019) provide insights on British behaviour relevant to Cyprus. Traditionally, the literature on tourism demand is largely dominated by studies of inbound expenditure (tourism export).…”
Section: Introductionmentioning
confidence: 99%